Cálculo del riesgo de adversidades climáticas para los cultivos: los cereales de verano en Monegros - Martí Ezpeleta, Alberto (Geographicalia, 2017)
The bigger or the lesser danger that happen climatic adversities on a region will determine the profitability and the possibility of growth for several crops on that region. This work presents one method to calculate the risk of unfavourable climatic occurrences during the crop growing. The summer cereals at the Monegros region are one example. The method is based at the valuation of the crop vulnerability grade to some climatic phenomenon and the occurrence probability of these phenomenon.